S.P. Raychaudhuri Memorial Lecture 2012 - Pragmatic characterization of fungal plant pathogens: some practical examples - BRIDGE, P.D. (Indian Phytopathology, 2013)
Accurate diagnosis of fungal plant diseases and the identification of the causative organism rely on combining information that may be obtained from a number of sources (Riley et al., 2002). This process will be dependent upon a number of considerations which include: • deciding the level of discrimination required • assessment of the methods available • consideration of genotypic or phenotypic variability in likely pathogen groups • reliability of reference data and materials Although in practice the pragmatic identification may be based primarily on a single criterion, the final decision will be influenced by various factors. Different methodologies can be combined to reach a single diagnosis, or may be useful as complementary methods to provide a broader understanding of the fungal ecology and the disease process.